The geopolitics of globalization : the consequences for development - Nayar, Baldev Raj. (New Delhi : Oxford University Press, 2005)
This book explores the role of geopolitics in the contemporary structuring of globalization. It looks at the nature of globalization and how it is influenced by markets and geopolitics, focusing on the developmental success in the original `Asian Tigers' (Japan, Korea, and Taiwan), China, and the members of the Association of Southeast Asian Nations. The book also examines the interaction between geopolitics and economic policy in India and Pakistan.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Globalization -- Political aspects; Geopolitics